PERAN INOVASI, LITERASI KEUANGAN, MODAL KERJA DAN KEBIJAKAN PEMERINTAH DALAM UPAYA MENINGKATKAN KINERJA UKM - Tara Widiarti S (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract. Business performance is generally used for part or all of the actions of a company in a certain period. The purpose of this study was to examine the role of innovation, financial literacy, working capital and government policies in an effort to improve the performance of SMEs. The population in this study were all SMEs in East Java Province. Respondents in this study were SME managers. The sampling technique used in this research is purposive sampling technique. The data used in this study is primary data because the data obtained directly from respondents in the form of questionnaires. The method used in this study is a survey method because the data source in this study uses a questionnaire. This study uses partial regression analysis to test the four hypotheses proposed in this study. Each hypothesis will be analyzed using PLS software to test the relationship between variables. Innovation, bookkeeping literacy and working capital can improve the performance of SMEs, while debt literacy, budgeting literacy and government policies are not able to improve the performance of SMEs.